Effectiveness and Anticancer Activity of a Novel Phenolic Compound from Garcinia porrecta Against the MCF-7 Breast Cancer Cell Line in vitro and in silico - Darwati D; Safitri AN; Ambardhani N; Mayanti T; Nurlelasari N; Kurnia D (Dove Medical Press, 2021)
Darwati Darwati, Ayu Nadila Safitri, Nurul Ambardhani, Tri Mayanti, Nurlelasari Nurlelasari, Dikdik Kurnia Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Padjadjaran, Jatinangor, 45363, West Java, IndonesiaCorrespondence: Darwati DarwatiDepartment of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Padjadjaran, Jatinangor, 45363, West Java, IndonesiaEmail darwati@unpad.ac.idBackground: Cancer is a leading cause of death worldwide, with breast cancer being the most common invasive cancer type in women. Several therapeutic strategies have been explored to reduce the mortality rates of breast cancer. Chemotherapy is the most commonly used systemic treatment, but associated with numerous side-effects. Development of anticancer agents with high efficacy and minimal negative effects is therefore an important focus of research. Natural materials provide an excellent source of bioactive compounds. For instance, Garcinia porrecta from the Clusiaceae family has multiple pharmacological activities, including antioxidant, anti-inflammatory, antibacterial, antiviral, anti-HIV, antidepressant, and anticancer properties.Purpose: The main objective of this study was to investigate the potential anticancer effects of compounds extracted from the bark of G. porrecta.Materials and Methods: Our experiments were divided into three steps: (1) chromatographic isolation of compounds using various separation techniques, such as extraction, separation and purification, (2) characterization via infrared (IR), nuclear magnetic resonance (NMR) and mass spectroscopy, and (3) evaluation of anticancer activity in vitro (MTT assay) and in silico (via analysis of molecular docking against caspase-9, tumor necrosis factor alpha (TNF-α), estrogen receptor alpha (ER-α), and human epidermal growth factor receptor 2 (HER-2)).Results: Depsidone ( 1) and benzophenone ( 2) from the ethyl acetate extract of bark of G. porrecta were identified as bioactive components. Examination of the activities of these compounds against MCF-7 cells revealed an IC50 value of 119.3 μg/mL for benzophenone, whereas IC50 for depsidone could not be estimated. Benzophenone activity was lower than that of the positive control doxorubicin (6.9 μg/mL). Depsidone showed the highest binding affinity for HER-2 (− 9.2 kcal.mol-1) and benzophenone for ER-α (− 8.0 kcal.mol-1).Conclusion: Benzophenone displays potency as an anticancer agent through blocking ER-α.Keywords: Garcinia porrecta, Clusiaceae, phenolic, MCF-7 cells, in vitro, in silico